(untitled) (Reflection and Critique Law Magazine, 2022)
The Law No. 11,340 of August 7, 2006 (known as the “Maria da Penha Law”) has won numerous victories regarding the legislation on the protection of women. It must be considered a late but very important achievement; especially front of Brazilian history of laws that marginalized women and strengthened social conservatism. This article, based on a hermeneutic study of the successive Brazilian legislations regarding the female condition, sought to analyze the innovative character of the Law No. 11.340, of August 7, 2006. It is concluded that that this law represented a great advance in the effort to consolidate respect for human rights in Brazil.